2015
DOI: 10.1016/j.jnnfm.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The non-monotonic shear-thinning flow of two strongly cohesive concentrated suspensions

Abstract: The behaviour in simple shear of two concentrated and strongly cohesive mineral suspensions showing highly non-monotonic flow curves is described. Two rheometric test modes were employed, controlled stress and controlled shear-rate. In controlled stress mode the materials showed runaway flow above a yield stress, which, for one of the suspensions, varied substantially in value and seemingly at random from one run to the next, such that the up flow-curve appeared to be quite irreproducible. The down-curve was n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…CaCO3 [1] φ=0.4 Peak stress on flow start--up @ constant shear--rate. 1 0.5 -1 (rate--dep t ) Strain sweep or staircase.…”
Section: Test Protocol Behaviourmentioning
confidence: 99%
See 3 more Smart Citations
“…CaCO3 [1] φ=0.4 Peak stress on flow start--up @ constant shear--rate. 1 0.5 -1 (rate--dep t ) Strain sweep or staircase.…”
Section: Test Protocol Behaviourmentioning
confidence: 99%
“…0.56 0.26 -0.36 Extrapolation from flow curve. 0.13 0 In [1] it was suggested that modifying or extending the Herschel-Bulkley equation [3] thus could account for the flow curves obtained by controlled rate testing,…”
Section: Test Protocol Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…At higher volume fractions (the subject of this paper), there is no universal theory of attractive particle rheology and flow properties depend on the details of the interparticle interactions. Strongly cohesive suspensions can display steep shear thinning and non-monotonic flow curves [37,38]. When making rheological measurements on such systems, pseudo-plasticity introduces problems in simple geometries.…”
Section: Introductionmentioning
confidence: 99%